Effect of ingestion and waterborne routes under different shrimp densities on white spot syndrome virus susceptibility in three commercially important penaeid shrimps - Raja, Kuzhanthaivel; Rahman, Mohammad Mustafizur; Rajkumar, Mayalagu; Gopalakrishnan, Ayyaru; Vijayakumar, Ramalingam (Elsevier B.V., 2015)
A study was undertaken to evaluate some factors that are important for better management of the whitespot syndrome virus (WSSV). We examined the likelihood of that the mud crab (Scylla serrata) is a potential carrier of WSSV in shrimp farms and then compared susceptibility of three shrimp species to WSSV,and finally tested the effects of shrimp stocking density and transmission routes on the intensity of WSSV infection under experimental conditions. Mud crabs were collected from the crab fattening unit of Pichavaram mangroves area, southeast coast of India. The infectivity test was conducted on Penaeus monodon, P. indicus, Litopenaeus vannamei under three different shrimp densities and two different routes of infection. Each treatment was executed in triplicate of 100 L tanks. The results showed that S. serrata is a carrier of WSSV. Among three species of shrimps, P. indicus was most susceptible and L. vannamei wasmost resistant in term of cumulative mortality. Ingestion route was more effective than waterborne routeon WSSV outbreaks. Cumulative mortality of shrimps due to WSSV infection increased with increasing shrimp density. The result of this study is important to improve management especially to minimize the WSSV infection in the shrimp farms.